Law-making Process in Indonesia An Analysis On the National Legislation Program (Prolegnas) - Akhmad Safik (Jurnal Magister Ilmu Hukum, 2016)
Abstract- Indonesia is the largest archipelago country in the world that consists of five large islands: Sumatra, Java, Kalimantan (Borneo), Sulawesi (Celebes), and Papua and some 18.000 smaller islands. The distance from Sabang district, a city in the most north-western top of Aceh on Sumatra to Merauke district, the most eastern border with Papua New Guinea is approximately 4,000 km. Most of its population, approximately 140 million live on Java, the smallest of large islands, which makes the island of 132,000 km2 one of the most densely populated areas in the world. The population is consisted by thousands many diverse ethnicities, cultures, traditions, linguistic and religious groups. The fact that Indonesia is one of the most socio-culturally diverse countries in the world is reflected by the symbol of Indonesia motto: unity in diversity. Therefore, the founding father of Indonesia declared Indonesia as the Unitary State of the Republic of Indonesia (Negara Kesatuan Republik Indonesia/NKRI). The Indonesian government is divided into three levels of administrations namely the Central Government, the Provincial Government and the Municipal/Regency Government. The Central Government, Provincial Government, Municipal/Regency Government is led by an elected president, an elected governor, and an elected regent/mayor, respectively. Every 5 years, the president, the governor and the regent/mayor are elected through the national, provincial and municipal/regency direct election. Key Words: country, Government, election